Impact of land use on urban mobility patterns, emissions and air quality in a Portuguese medium-sized city - Bandeira, Jorge Filipe Marto (2011)
The main objective of this work was to evaluate the impact of urban development trends in mobility patterns of a medium sized Portuguese city and air quality consequences, using a sequential modeling process, comprising i) land use and transportation, TRANUS model; ii) road traffic air pollutants emissions, TREM model and; iii) air quality, TAPM model. This integrated methodology was applied to a medium sized Portuguese city. In order to evaluate the implementation of the methodology, a preliminary study was performed, which consisted on the comparison of modeled mobility patterns and CO and PM(10) concentrations with measured data used in the definition of the current scenario. The comparison between modeled and monitored mobility patterns at the morning peak hour for a weekday showed an RMSE of 31%. Regarding CO concentrations, an underestimation of the modeled results was observed. Nevertheless, the modeled PM(10) concentrations were consistent with the monitored data. Overall, the results showed a reasonable consistency of the modeled data, which allowed the use of the integrated modeling system for the study scenarios. The future scenarios consisted on the definition of different mobility patterns and vehicle technology characteristics, according to two main developing trends: (1) "car pooling" scenario, which imposes a mean occupancy rate of 3 passengers by vehicle and (2) the "Euro 6" scenario, which establishes that all vehicles accomplish at least the Euro 6 standard technology. Reductions of 54% and 83% for CO, 44% and 95% for PM(10), 44% and 87% for VOC and 44% and 79% for NO(x) emissions were observed in scenarios 1 and 2, respectively. Concerning air quality, a reduction of about 100 mug m(-3) of CO annual average concentration was observed in both scenarios. The results of PM(10) annual concentrations showed a reduction of 1.35 mug m(-3) and 2.7 mug m(-3) for scenarios 1 and 2 respectively.